Recent advances in analytical techniques. - Rahman, Atta-ur-, 1942-; Ozkan, Sibel A. (Bentham Science Publishers Pte. Ltd., 2022)
"The fifth volume of the series features five reviews which demonstrate chemical analysis techniques applied in different disciplines."-- Provided by publisher
Keywords: Analytical chemistry -- Technique.; Analytical chemistry -- Technological innovations.; Chimie analytique -- Technique.; Chimie analytique -- Innovations.; Analytical chemistry -- Technique